Synaptogenesis in the rat suprachiasmatic nucleus demonstrated by electron microscopy and synapsin I immunoreactivity - Moore, RY (J Neurosci, 1989)
Synaptogenesis was studied in the rat suprachiasmatic nucleus (SCN) using quantitative ultrastructural analysis and synapsin I immunohistochemistry. SCN neurons are formed between embryonic days 13 and 17 (E13-E17), and the SCN is a distinct hypothalamic nucleus by E18. At E19 the nucleus is very immature and there are few synapses. Synaptogenesis proceeds slowly until P4 but increases rapidly between P4 and P10. At P10 the number of synapses per unit area is the same as in the adult SCN and all synaptic types present in the adult are evident. However, the SCN continues to increase in volume to the adult with approximately 30% of total synaptic number added between P10 and a young adult age. The appearance of synapsin I immunoreactivity correlates very precisely with the development of synapses in the SCN as shown by ultrastructural analysis between E19 and P6. The pattern of appearance of synapsin I immunoreactivity demonstrates that synaptogenesis in the SCN is significantly delayed in comparison to adjacent hypothalamic nuclei. Synapsin I immunohistochemistry is a reliable marker of synapse formation in the developing SCN. A correlation of these anatomical data with prior functional studies suggests that SCN neurons are born as individual circadian oscillators that undergo a rapid development in the first 10 days after birth to form a functional neural network subserving circadian rhythm generation and regulation.